Conhecimento e linguagem: um estudo do Teeteto de Platão - Zeni, Eleandro Luis (2012)
The dialectic discussion developed in Theaetetus aims to find the only definition of knowledge to which determines all wisdom. Through maieutics, the method of bringing to earth the knowledge grown in the soul of a speaker, Socrates extracts from the young geometra Theaetetus three definitions for episteme which are not kept: (1) the episteme as a sensation (aisthesis); (2) the episteme as a true opinion (alethes doxa); and, (3) the episteme as a true opinion accompanied by rational explanation or logos (alethes doxa meta logou). We will reconstruct, in this dissertation, the structure of the three definitions of episteme. The objective is to investigate the Platonic argumentation in Theaetetus concerning the issues of knowledge and languages, more precisely, the meaning of logos – propositions in the process of knowledge. Theaetetus, the first piece to treat in an explicit way about the episteme, has influenced, in a more or less clear way, the investigations around the nature and the possibility of human knowledge. Language problems that emerged in Theaetetus, and in other closer dialogs, also persist in a more or less explicit way in the contemporary discussions around the possibility and the ways language describes the world. However, a possible questioning is if the platonic conception of knowledge is equal to the one from the philosophers of today. Contemporaneously, there are two groups of experts which diverge in the way of interpreting the issue of knowledge proposed in Theaetetus: one, which supposes that Plato had in mind something different from what, in our time, we call knowledge, assures that the platonic notion of episteme would be equal to knowledge of things through an immediate cognitive apprehension, a mental grasp; another, which tries to approximate Plato’s opinion to the contemporaries’ opinions, and supports that the knowledge to which Socrates refers to in Theaetetus is the knowledge about the truth of facts or propositional truth. This way, we aim in this dissertation, to do an approach of interpretative problems referent to knowledge and language which emerge in abundance in Theaetetus.